2006
DOI: 10.1097/01.ijg.0000212217.19804.a7
|View full text |Cite
|
Sign up to set email alerts
|

Association of Apolipoprotein E Polymorphisms With Normal Tension Glaucoma in a Chinese Population

Abstract: Our findings suggest that the APOE epsilon 4 allele confers a protective effect against NTG, whereas the APOE promoter polymorphisms do not contribute to POAG risk. However, the APOE -219G carriers tended to have later-onset POAG.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(32 citation statements)
references
References 39 publications
1
26
0
Order By: Relevance
“…23 However, the other studies have not confirmed the relationship of -491 A/T APOE polymorphism with POAG. 24,25 The promoter polymorphisms -219 T/G and -427 T/C of the APOE gene were also not associated with glaucoma. 26 There is also evidence that the presence of specific isoforms of the APOE gene may affect glaucoma development.…”
Section: Discussionmentioning
confidence: 91%
“…23 However, the other studies have not confirmed the relationship of -491 A/T APOE polymorphism with POAG. 24,25 The promoter polymorphisms -219 T/G and -427 T/C of the APOE gene were also not associated with glaucoma. 26 There is also evidence that the presence of specific isoforms of the APOE gene may affect glaucoma development.…”
Section: Discussionmentioning
confidence: 91%
“…Five eligible studies were not include in the meta-analysis [13,15,17,21,23]. Meanwhile, two studies contained overlapping data [19,39], and only the largest study [19] should be selected for the analysis. In another study by Wang et al [28], there were many mistakes in the data extraction (see Supplementary Table two in their article).…”
Section: Discussionmentioning
confidence: 99%
“…Vickers et al [11], Al-Dabbagh et al [12] and Yuan et al [10] reported that the Apo E ε4 gene is associated with elevated risk of POAG or NTG. On the contrary, Lam and his colleagues [13] reported that the Apo E ε4 gene confers a protective effect against NTG. Their findings, however, could not be replicated in other researchers [14], [15], [16], [17], [18], [19], [20].…”
Section: Introductionmentioning
confidence: 95%